The role of business model innovation as mediating and environmental dynamism as moderating variable to improve performance in Indonesia - Arifin, Johan; Prabowo, Harjanto; Hamsal, Mohammad; Elidjen, Elidjen (International Journal of Innovative Research and Scientific Studies, 2025)
This study investigates the role of Business Model Innovation (BMI) as a mediator between Lean Construction (LC), Supply Chain Resilience (SCR), Strategic Partnership (SP), and Environmental Dynamism (ED) on Firm Performance (FP) in the Indonesian construction industry. It explores both the direct impacts of these practices and their indirect effects through business model innovation transformation. A quantitative approach was used with survey data from 226 C-level and senior managerial respondents across major construction firms. Structural Equation Modelling (SEM) with SmartPLS tested eight hypothesised relationships among LC, SCR, SP, BMI, ED, and FP. The results show that Lean Construction significantly improves Firm Performance, both directly and indirectly through BMI, with the mediated path stronger than the direct effect. Strategic Partnership does not directly affect FP but has a positive indirect impact when mediated by BMI. This research underscores BMI as a crucial bridge linking lean practices and partnerships to stronger performance. It encourages construction firms to combine lean methods and strategic partnerships with innovative business model design to improve competitiveness and resilience. Future research should consider longitudinal analysis, cross-industry comparisons, and contextual factors such as digital maturity and regulation.